Experimental determination of viscosity of Water-Glycerine based Cu nano-fluids. (2019) - Lahari, M.L.R. Chaitanya; Sai, P.H.V. Sesha Talpa; Narayanaswamy, K.S.; HaseenaBee, P.; Devaraj, S.; Sharma, K.V.
Abstract: Dispersion of nano sized metallic particles in to conventional base fluids, called nano-fluids, is expected to yield enhanced heat transfer properties. Experimental determination and subsequent correlations of thermo-physical properties such as viscosity, thermal conductivity, specific heat capacity etc., of these nano-fluids become necessary to estimate the heat transfer performance of these nano-fluids. Cu nano-fluids in Water-Glycerine base fluids are prepared at different volume concentrations of Cu nano particles. Two step dispersion synthesis method, without using any surfactant, is used to prepare nano-fluids consisting of Cu nano-particles in Water-Glycerine base fluid. Viscosity of these nano-fluids is determined experimentally at different temperatures of 20, 40, 60 and 80 °C using Brookfield Viscometer. Three different volume concentrations of Cu-based nano-particles in the base fluid are taken as 0.2%, 0.6% and 1.0%. SEM and EDS images show the particle size distribution and elemental analysis of Cu nano-particles. It has been observed that viscosity of nano-fluids increased with increase in particle volume concentration and decreased with increase in fluid temperature. Maximum viscosity value of 3.76 cP for 1.0% vol. concentration at 20 °C and minimum viscosity value of 0.94 cP at 80 °C for 0.2% vol. concentration is obtained for copper nano-fluids. Viscosity for Water-Glycerine base fluid also measured at different temperatures of 20, 40, 60 and 80 °C. This viscosity data of will be useful for the aspiring researchers to predict heat transfer properties of copper nano-fluids.